2015
DOI: 10.1002/psp4.12047
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative prediction and clinical evaluation of an unexplored herb–drug interaction mechanism in healthy volunteers

Abstract: Quantitative prediction of herb–drug interaction risk remains challenging. A quantitative framework to assess a potential interaction was used to evaluate a mechanism not previously tested in humans. The semipurified milk thistle product, silibinin, was selected as an exemplar herbal product inhibitor of raloxifene intestinal glucuronidation. Physiologically based pharmacokinetic (PBPK) model simulations of the silibinin–raloxifene interaction predicted up to 30% increases in raloxifene area under the curve (A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 42 publications
0
16
0
Order By: Relevance
“…However, data obtained in vitro is very often required to plan and undertake a robust clinical assessment. In addition, it has now been shown that given the availability of in vitro data, physiologically based pharmacokinetic (PBPK) modeling and simulation tools can be used as an alternative means for the quantitative prediction of HDIs without the need for clinical studies (Brantley et al, 2014 ; Gufford et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, data obtained in vitro is very often required to plan and undertake a robust clinical assessment. In addition, it has now been shown that given the availability of in vitro data, physiologically based pharmacokinetic (PBPK) modeling and simulation tools can be used as an alternative means for the quantitative prediction of HDIs without the need for clinical studies (Brantley et al, 2014 ; Gufford et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…21,125 GMP producers certify that their products are consistently produced and controlled according to quality standards. Whether the product is custom formulated 21 or obtained from commercial sources, testing is required for contaminants, including "heavy metals, microbial limits, residual pesticides, adventitious toxins (e.g., aatoxins), [and] endogenous toxins (e.g., pyrrolizidine alkaloids)" according to 21 CFR 111.70(b) (3). Product batches that do not meet the limits of contamination must be rejected.…”
Section: Consideration Of Contaminationmentioning
confidence: 99%
“…More than 50% of Americans acknowledge taking dietary supplements, 1,2 with sales more than tripling since passage of the Dietary Supplement Health and Education Act in 1994. 3,4 In many cases, these dietary supplements are prepared from Dr Joshua J. Kellogg obtained his PhD in natural product chemistry and ethnobotanical nutraceuticals from North Carolina State University. He is currently a researcher in the lab of Professor Nadja Cech at the University of North Carolina at Greensboro, investigating the relative contributions of natural product mixtures to antibacterial activity.…”
Section: Introductionmentioning
confidence: 99%
“…Brantley et al . and Gufford et al . have managed to make quantitative HDI predictions for milk thistle's ( Silybum marianum ) effect on CYP3A4, CYP2C9, and various UGT1A isoforms using PBPK modeling.…”
Section: Herb‐drug Interactions: a Question Of Clinical Relevancementioning
confidence: 99%